Earning Informativeness is Moderating Investment Opportunity, Return on Asset, and Leverage on Prudence Measurement - Malau, Melinda (Journal of Accounting, Business and Finance Research, 2020)
This study aims to analyze whether earning informativeness can moderate the effect investment opportunity, return on asset, and leverage on the prudence measurement. The method used in this study is a panel regression analysis. The sample used in the study was 500 observations using data from manufacturing companies for the period 2014-2018. The results of the first model show that investment opportunity has a significant positive effect on prudence. Return on asset has a significant positive effect on prudence. Leverage has a significant positive effect on prudence. The results of the second model show earning informativeness strengthens the effect of investment opportunity on prudence. Earning informativeness strengthens the effect of return on asset on prudence. Earning informativeness strengthens the effect of leverage on prudence. The implication of this study that funding decisions made inaccurately will cause fixed costs and subsequently result in a low profitability of a company. High profit quality accurately reflects the company’s operational performance.